2018
DOI: 10.1080/14786419.2018.1528593
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of fucoxanthin on dextran sulfate sodium-induced colitis in mice

Abstract: The anti-inflammatory activities of fucoxanthin, a marine carotenoid derived from the macroalgae and microalgae, have been demonstrated in the previous studies. However, the effect of fucoxanthin on ulcerative colitis (UC), an inflammatory bowel disease, was still unclear. In this study, we evaluated the in vivo anti-inflammatory effect of fucoxanthin on dextran sulfate sodium(DSS)-induced colitis in mice. Fucoxanthin at the doses of 50 and 100 mg/kg/day significantly protected against DSSinduced gradual loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 14 publications
(1 reference statement)
1
35
0
Order By: Relevance
“…The results revealed that the FX-mediated anti-inflammation function is associated with the activation of NF-κB ( Figures 5 – 9 ), which is consistent with the findings of previous studies, and have shown that FX can inhibit NO synthase and cyclooxygenase protein, and reduced the expression of NO and prostaglandin E2 levels, by inhibiting the activation of NF-κB and phosphorylation of MAPK (Kim et al, 2010). Numerous studies have reported that FX suppresses LPS-induced overexpression of iNOS and COX-2, as well as pro-inflammatory cytokines production in vitro and in vivo (Shiratori et al, 2005; Kim et al, 2010; Heo et al, 2012; Islam et al, 2013; Lee et al, 2013; Pangestuti et al, 2013; Robertson et al, 2015; Choi et al, 2016; Zhao et al, 2017; Jiang et al, 2018; Jung et al, 2018; Yang et al, 2018), which is similar to our findings. As the previous studies reported, the anti-inflammatory mechanism of FX involved NF-κB pathways (Kim et al, 2010b; Robertson et al, 2015; Zhao et al, 2017; Jiang et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The results revealed that the FX-mediated anti-inflammation function is associated with the activation of NF-κB ( Figures 5 – 9 ), which is consistent with the findings of previous studies, and have shown that FX can inhibit NO synthase and cyclooxygenase protein, and reduced the expression of NO and prostaglandin E2 levels, by inhibiting the activation of NF-κB and phosphorylation of MAPK (Kim et al, 2010). Numerous studies have reported that FX suppresses LPS-induced overexpression of iNOS and COX-2, as well as pro-inflammatory cytokines production in vitro and in vivo (Shiratori et al, 2005; Kim et al, 2010; Heo et al, 2012; Islam et al, 2013; Lee et al, 2013; Pangestuti et al, 2013; Robertson et al, 2015; Choi et al, 2016; Zhao et al, 2017; Jiang et al, 2018; Jung et al, 2018; Yang et al, 2018), which is similar to our findings. As the previous studies reported, the anti-inflammatory mechanism of FX involved NF-κB pathways (Kim et al, 2010b; Robertson et al, 2015; Zhao et al, 2017; Jiang et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Fucoxanthin preventive anti-inflammatory effect in a mouse model of Sepsis is associated with the regulation of NF-κB signaling [20]. Fucoxanthin downregulates the DSS-induced expression of COX-2 and NF-κB in mice [21]. Fucoxanthin inhibited LPSinduced overexpression of pro-inflammatory cytokines (IL-1β, IL-6, iNOS, COX-2, and TNF-α) via the AMPK/NF-κB signaling pathway [16].…”
Section: Introductionmentioning
confidence: 99%
“…Fucoxanthin, a red marine carotenoid found in seaweeds, has been known to be effective against inflammation, diabetes, cancer, and obesity. In a lipopolysaccharide-induced murine macrophage RAW 264.7 cell model, FX produced an anti-inflammatory effect by inhibition of nitric oxide, prostaglandin, IL-6, IL-8, IL-1β, through NF-kB suppression and MAPK phosphorylation [14]. It has been reported that FX reduces the activity of monocyte chemoattractant protein-1 (MCP-1) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Fucoxanthin (FX), a non-provitamin-A marine carotenoid, is known to possess activities against inflammation, oxidative stress, cancer, diabetes, and obesity. Anti-inflammatory effect of FX has been proved against lipopolysaccharide-induced inflammation in murine RAW 264.7 culture system [14]. Neuroinflammation, induced by amyloid-β42 and lipopolysaccharide in BV2 microglia cells can be regulated through negative feedback by FX [15].…”
Section: ------------------------------------------------------------mentioning
confidence: 99%